Novel hydroxyapatite/chitosan bilayered scaffold for osteochondral tissue-engineering applications : scaffold design and its performance when seeded with goat bone marrow stromal cells - Oliveira, Joaquim M. (2006)
Recent studies suggest that bone marrow stromal cells are a potential source of osteoblasts and chondrocytes and can be used to regenerate damaged tissues using a tissue-engineering (TE) approach. However, these strategies require the use of an appropriate scaffold architecture that can support the formation de novo of either bone and cartilage tissue, or both, as in the case of osteochondral defects. The later has been attracting a great deal of attention since it is considered a difficult goal to achieve. This work consisted on developing novel hydroxyapatite/chitosan (HA/CS) bilayered scaffold by combining a sintering and a freeze-drying technique, and aims to show the potential of such type of scaffolds for being used in TE of osteochondral defects. The developed HA/CS bilayered scaffolds were characterized by Fourier transform infra-red spectroscopy, X-ray diffraction analysis, micro-computed tomography, and scanning electron microscopy (SEM). Additionally, the mechanical properties of HA/CS bilayered scaffolds were assessed under compression. In vitro tests were also carried out, in order to study the water-uptake and weight loss profile of the HA/CS bilayered scaffolds. This was done by means of soaking the scaffolds into a phosphate buffered saline for 1 up to 30 days. The intrinsic cytotoxicity of the HA scaffolds and HA/CS bilayered scaffolds extract fluids was investigated by carrying out a cellular viability assay (MTS test) using Mouse fibroblastic-like cells. Results have shown that materials do not exert any cytotoxic effect. Complementarily, in vitro (phase I) cell culture studies were carried out to evaluate the capacity of HA and CS layers to separately, support the growth and differentiation of goat marrow stromal cells (GBMCs) into osteoblasts and chondrocytes, respectively. Cell adhesion and morphology were analysed by SEM while the cell viability and proliferation were assessed by MTS test and DNA quantification. The chondrogenic differentiation of GBMCs was evaluated measuring the glucosaminoglycans synthesis. Data showed that GBMCs were able to adhere, proliferate and osteogenic differentiation was evaluated by alkaline phosphatase activity and immunocytochemistry assays after 14 days in osteogenic medium and into chondrocytes after 21 days in culture with chondrogenic medium. The obtained results concerning the physicochemical and biological properties of the developed HA/CS bilayered scaffolds, show that these constructs exhibit great potential for their use in TE strategies leading to the formation of adequate tissue substitutes for the regeneration of osteochondral defects.